Sustainability of Impact: Dimensions of Decline and Persistence in Adoption of a Biofortified Crop in Uganda - International Food Policy Research Institute; University of California, Davis; Nutridemics (International Food Policy Research Institute, 2015)
This study examines the sustainability of the impact of a biofortification program that introduced provitamin-A-rich orange-fleshed sweet potatoes (OSP) to farming households in Uganda. The crop was introduced in a randomized controlled experiment to test the impact and cost-effectiveness of introducing OSP on crop adoption and dietary intakes of vitamin A. A previous impact evaluation of the two-year project using baseline and endline data found large impacts on both OSP adoption and vitamin A consumption in project households. This study examines the sustainability of the intervention by studying the profile of OSP adoption during the project and over four seasons after the project’s end.